Referenciais para a detecção, seleção e promoção de talentos esportivos em GRD - Lanaro Filho, P. (Escola de Educação Física e Esporte, Universidade de São Paulo, 2001)
The general objective of this study was the establishment of referentials to be used in the detection, selection and promotion of sports talents in the field of Rhythmic Gymnastics. A two-phase descriptive research was carried out for this purpose. In the first phase, we tried to verify the understanding that Brazilian coaches have about issues related to sports talents in this area. In order to accomplish our goals, we analyzed the questionnaires answered by a sample of 26 coaches from six different States. The second phase meant to characterize the athletes from the Brazilian Rhythmic team in regard to maturity, anthropometry and flexibility. Several variables measured from a sample of eight gymnasts from the 2000 Olympic Brazilian team were analyzed. Finally, convergent and divergent aspects of the common variables from both phases in the research were verified. As for the results, we could see that the coaches have an understanding of issues related to sports talents very close to that of high levei Brazilian gymnasts and these gymnasts have characteristics similar to those of high levei gymnasts under research in other countries. Based on the results, we conclude that this study can be used as a referential for the detection, selection and promotion of high performance talents in Rhythmic Gymnastics